The evaluation of anaemia in an older primary care population: retrospective population-based study - David McCartney; Brian Shine; Deborah Hay; Daniel S Lasserson (BJGP Open, 2017)
Background: Anaemia is common in older people and the identification of potentially reversible haematinic deficiencies relies on appropriate investigation, often undertaken in primary care. Aim: To determine the laboratory prevalence of anaemia, the types of anaemia observed, and the biochemical and haematological investigations undertaken to characterise any associated haematinic abnormality in older primary care patients. Design & setting: A retrospective primary care based study of patients aged >65 years undergoing a full blood count in Oxfordshire, UK between 1 January 2012 and 31 December 2013 Method: Consecutive patients aged >65 years with a full blood count were identified retrospectively from a laboratory database. Patient demographics, number of blood tests and additional laboratory investigations requested were recorded. World Health Organisation (WHO) criteria were used to define anaemia. Results: In total 151 473 full blood counts from 53 890 participants were included: 29.6% of patients were anaemic. The majority had a normocytic anaemia (82.4%) and 46.0% of participants with anaemia had no additional investigations performed. The mean haemoglobin was lower in the anaemic group that underwent further investigation than those who did not (Hb 10.68 g/dl versus 11.24 g/dl, P<0.05): 33.2 % of patients with a microcytic anaemia (mean cell volume <80) did not have any markers of iron status measured. Conclusion: A large proportion of older adults in primary care with a recent blood test are anaemic, the majority with a normocytic anaemia, with evidence of inadequate investigation. Those with lower haemoglobin are more likely to be further investigated. Further work is needed to understand the approach to anaemia in older adults in primary care.